1990
DOI: 10.1056/nejm199005243222107
|View full text |Cite|
|
Sign up to set email alerts
|

Relation of Cytogenetic Abnormalities and Clinical Outcome in Metastatic Melanoma

Abstract: The value of chromosomal analysis is well established in human hematologic neoplasms. In contrast, the relation between chromosomal abnormalities and clinical outcome in solid tumors in humans has received little study. We undertook this study to determine whether chromosomal abnormalities could provide information on the survival of patients with malignant melanoma. Chromosome-banding analysis was performed on tumor-biopsy samples from 62 patients with metastatic melanoma, and recurring cytogenetic abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 10 publications
4
38
0
1
Order By: Relevance
“…Several other preclinical parameters have been reported to correlate with disease progression in melanoma, including cytogenetic abnormalities, DNA ploidy and S-phase fraction, the expression of metastasis associated gene products, elevated serum levels of soluble adhesion molecules and the detection of circulating melanoma cells in peripheral blood using reverse transcription-polymerase chain reaction (RT-PCR) for tyrosinase messenger RNA (Trent et al, 1990;Smith et al, 1991;Xerri et al, 1994;Karlsson et al, 1996;Kunter et al, 1996). These parameters could reflect increase in the total tumour mass, recurrence of the disease or the presence of occult melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…Several other preclinical parameters have been reported to correlate with disease progression in melanoma, including cytogenetic abnormalities, DNA ploidy and S-phase fraction, the expression of metastasis associated gene products, elevated serum levels of soluble adhesion molecules and the detection of circulating melanoma cells in peripheral blood using reverse transcription-polymerase chain reaction (RT-PCR) for tyrosinase messenger RNA (Trent et al, 1990;Smith et al, 1991;Xerri et al, 1994;Karlsson et al, 1996;Kunter et al, 1996). These parameters could reflect increase in the total tumour mass, recurrence of the disease or the presence of occult melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations on cutaneous melanoma have demonstrated that multiple genetic abnormalities exist within these tumours (reviewed in Rees and Healy, 1996). Cytogenetic studies have detected gains and losses of genetic material on multiple chromosomes, and subsequent studies on loss of heterozygosity (LOH) have con®rmed the ®nding of frequent allelic loss (Cowan et al, 1988;Dracopoli et al, 1989;Trent et al, 1990;Millikin et al, 1991;Fountain et al, 1992;Isshiki et al, 1993Isshiki et al, , 1994Herbst et al, 1994;Holland et al, 1994;Walker et al, 1994;Healy et al, 1995Healy et al, , 1996aThompson et al, 1995). Recent work has shown that 6q, 9p and 10q are the chromosome arms most frequently lost in this tumour, with evidence that allelic losses on 6q and 10q may be responsible for the malignant phenotype in this neoplasm (Healy et al, 1996a).…”
Section: Introductionmentioning
confidence: 90%
“…Some (but not all) studies on DNA ploidy in melanoma have suggested that individuals with tumours exhibiting aneuploidy have a poorer outcome, but there is little information on which chromosomes are responsible for this (Muhonen et al, 1992;Heaton et al, 1993;Scheistroen et al, 1995;Umebayashi and Otsuka, 1995). Trent et al (1990) investigated metastatic melanomas for cytogenetic aberrations in relation to clinical outcome, and documented that individuals with structural abnormalities of chromosomes 7 and 11 had signi®cantly shorter survival than patients without these abnormalities. However, metastatic melanoma is a late stage of disease, and nearly all patients with metastases will eventually die from their melanoma (Barth et al, 1995;Lee et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained are quite complex and not always unambiguous. However, the non-random involvement of chromosomes 1, 6, 7 and 9 has been published repeatedly (Chen et al, 1973;Koprowski et al, 1985;Heim et al, 1988;Trent at al, 1990;Balch et al, 1992). Deletions or loss of function of the p53 tumour-suppressor gene (p53-TSG) have been found in roughly 50% of all malignant tumours .…”
Section: Malignant Melanoma (Mm) Is a Common Cancer Amongmentioning
confidence: 99%